The Oxford handbook of modern African history - Parker, John, 1960-; Reid, Richard J. (Richard James) (New York : Oxford University Press, 2013)
"This collection of essays ... will allow readers to explore various aspects ... of the continent's history over the last two hundred years."--Book jacket.
Introduction : African histories : past, present, and future / Richard Reid and John Parker -- Key themes in African history. Ecology and environment / James McCann ; Demography and disease / Shane Doyle ; African slave trades in global perspective / Pier M. Larson ; States and statelessness / Walter Hawthorne ; Ethnicity and identity / Richard Waller ; Warfare and the military / Richard Reid ; The African diaspora / John Parker -- The colonial encounter. African colonial states / Heather J. Sharkey ; Law, crime, and punishment in colonial Africa / Richard Roberts ; Work and migration / Emily Lynn Osborn ; Chieftaincy / Justin Willis ; Between the present and history : African nationalism and decolonization / Jean Allman -- Religion and belief. Islam / Marie Miran-Guyon and Jean-Louis Triaud ; Christianity / David Maxwell ; Indigenous African religions / Robert M. Baum ; New religious movements / Sean Hanretta -- Society and economy. Education and literacy / Carol Summers ; Women and gender / Barbara M. Cooper ; Urbanization and urban cultures / John Parker ; Health and healing / Nancy Rose Hunt ; Youth / Nicolas Argenti and Deborah Durham ; Economic growth / Morten Jerven -- Arts and the media. Visual cultures / Sidney Littlefield Kasfir ; Music in modern African history / Viet Erlmann ; African literary histories and history in African literatures / Stephanie Newell ; Communications and media in African history / James R. Brennan.
Includes bibliographical references and index.
Keywords: Africa -- History; Africa -- 1801-1884.; Africa -- History -- 1884-1945.; Africa -- History -- 1945-1960.; Africa -- History -- 1960-; Afrika